Filipina migrant domestic workers' identity and narrative practices on social media from self to nation - Bancoro, Sharon V. (Quezon City Asian Center, University of the Philippines Diliman, 2022)
In real life and on social media, Filipina migrant domestic workers are excluded from the construction of their own collective identity. This brings to the surface the voices of Filipina migrant domestic workers in this process of constructing their collective identity. The study, which uses constructivist grounded theory, draws data from the personal online narratives of five migrant tellers that were originally published on the Facebook page Definitely Filipino and its blog site of the same name. Transcripts of the researcher's personal interviews with the tellers and the comment section of Definitely Filipino are also analyzed. This study aims to conceptualize how these migrant storytellers are able to construct a positive collective identity through their narrative practices on social media and to theorize how this collective identity construction is implicated in the notions of the Filipino nation in global context.

The result of this inquiry is the core category of huntahan. Huntahan is a communication circuit where the tellerrs use personal migration stories to talk to each other on social media and, in the process, produce a positive collective identity for their group. The narrative practices documented include publishing personal stories, constructing a positive collective identity through a number of strategies, and co-telling. This study argues that the version of positive collective identity by migrant tellers can shift the social signification of "domestic worker" in the international arena where the term is equated to "Filipino". Though this shift might not entirely deconstruct this correspondence, it can disrupt the negative social signification of "domestic worker" and has the potential to disrupt the meaning of the "Filipino" as well. The Filipina migrant storytellers in this digital space occupy a central position in the re-writing of the notion of "Filipino" held by people from labor-receiving countries and by fellow Filipina migrant domestic workers who have internalized such problematic notions.
P - the author wishes to publish the work personally
Keywords: Women migrant labor -- Philippines; Storytelling in mass media; Group identity